(untitled) (Economic studies journal, 2023)
Abstract The research aims to predict inflation rates in the Libyan economy using the Box-Jenkins methodology. The research concluded that the Libyan economy was subjected to inflationary waves during the period under study, which increased in severity in recent years, and the inflation rate will continue to rise during the medium-term forecast period until 2025 unless the concerned authorities take appropriate policies to address its causes. Inflation in Libya is a complex phenomenon. Part of it is related to the monetary aspect, and another part is related to stimulating demand due to excessive public spending, and another is due to external causes (imported inflation) Based on these results, the research recommends the need to raise the value of the Libyan dinar, based on the reality of the Libyan economy, which depends almost entirely on covering the needs of the local market through imports. As well as the independence of the Central Bank of Libya, controlling public spending, rationing bank lending and directing them towards productive projects, in a way that contributes to securing a minimum level of food security for citizens.